From nostalgia for the recent past and beyond: The temporal frames of recalled consumption experiences. (6th November 2017) - Ryynänen, Toni; Heinonen, Visa
Abstract: Studies of nostalgia are one of the research subfields of recalled consumption experiences. In addition to the nostalgic recall, the consumers' remembered experiences situate in other temporal frames, a theme rarely touched in the extant research. The aim of this research was to examine the differences between nostalgic and other recalled consumption experiences by identifying and analysing the characteristics of the temporal frames. The data set for this task comprised 480 descriptions of consumers' experiences involving an everyday consumer object. An interpretive approach was utilized to analyse the temporal frames. The results of the study indicate that the consumers described their memories in four temporal structures. These are the strong nostalgia from childhood, light nostalgia from youth, descriptions of recent past and memories linked to consumption practices and traditions that will be fostered in the future. The article proposes a conceptual framework describing the temporal frames of consumers' remembered consumption experiences that opens further avenues for research alongside of nostalgic recall.